Histopathological findings of renal tissue induced by oxidative stress due to different concentrations of fluoride - Luo, Qin (Oncotarget, 2017)
It has been reported that excessive intake of fluoride can induce renal lesions. However, its pathogenesis is still less understood. Therefore, this study was conducted to investigate oxidative damage and the relationships between the oxidative damage and renal lesions in fluoride-treated mice by using the methods of histopathology, biochemistry, flow cytometry and quantitative real-time polymerase chain reaction (qRT-PCR). A total of 240 ICR mice were randomly divided into four equal groups (sodium fluoride was given orally at the dose of 0, 12, 24 and 48 mg/kg body weight for 42 days, respectively). We found that fluoride in excess of 12 mg/kg induced renal oxidative damage, which was characterized by increasing the levels of reactive oxygen species (ROS) production and contents of malondialdehyde (MDA) and protein carbonyls (PC), and decreasing the abilities of anti-superoxide anion (ASA) and anti-hydroxyl radical (AHR), glutathione (GSH) content, as well as activities and mRNA expression levels of superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR) and glutathione peroxidase (GSH-Px). Concurrently, fluoride caused degeneration and necrosis of the tubular cells, renal tubular hyaline casts and glomeruli swelling, which were consistent with the alteration of renal function parameters including elevated contents of serum creatinine (Cr), serum uric acid (UA), blood urea nitrogen (BUN), and the activities of urinary N-acetyl-b-D-glucosaminidase (NAG), renal lactate dehydrogenase (LDH), and reduced activities of sodium-potassium adenosine triphosphatase (Na+/K+-ATPase) and acid phosphatase (ACP) in the kidney. The above-mentioned results showed that fluoride in excess of 12 mg/kg induced renal oxidative damage, which then caused renal lesions and dysfunctions. These findings also clearly demonstrated that oxidative damage is one of the mechanisms of fluoride-induced renal lesions and dysfunctions.